Regional Politics: Penetrating Indigenous Rights in Regional Expansion in Nagari Salareh Aia, Palembayan District, Agam Regency, West Sumatra Province in 2020 - Ishak; Ernanda, Oksa (Jurnal Bina Praja, 2021)
The regional expansion was carried out to facilitate access to public services. The implementation of regional expansion was initially carried out in defining territorial boundaries. In the demarcation of this territory, there are protests due to the lack of involvement of indigenous peoples. As residents of the original domicile, the indigenous peoples fight for their land ownership rights, which are involved in the regional expansion plan. It happened in the expansion of the Nagari Salareh Aia area, Palembayan District, Agam Regency. After the enactment of Regent Regulation No. 15 of 2017 regarding the preparation of Nagari guardians. There were many protests against the boundaries set by the government through these instruments. Researchers try to explore this phenomenon through social law by examining aspects of regional politics, in this case, the rights of indigenous peoples, social capital in conflict resolution, and an assessment of the impact of these two issues in resolving regional division conflicts. Through a set of studies and discussions, it was found that the government and the community must work together and make decisions that do not ignore regional wisdom. Through this synergy, it was hoped that regional expansion would be conducted appropriately, which can provide benefits to the community and regional government.